Robust Image-Based Streamflow Measurements for Real-Time Continuous Monitoring - Peña-Haro, Salvador; Carrel, Maxence; Lüthi, Beat; Hansen, Issa; Lukes, Robert (Frontiers in Water, 2021)
The volumetric flow rate in rivers is essential to analyze hydrological processes and at the same time it is one of the most difficult variables to measure. Image based discharge measurements possess several advantages, one of them being that the sensor (camera) is not in contact with the water, that it can be placed safe of floods, its mounting position is very flexible and there is no need of expensive structures/constructions. During the last years several image-based methods for measuring the surface velocity in rivers and canals have been proposed and successfully tested under different conditions. However, these methods have been used and configured to perform well under the particular conditions of a single recording or single experiment. In order to have a continuous 7x24 method that measures the volumetric flow under different conditions day and night and all year long, the method has to be able to perform in rivers or canals of different sizes and flow velocities and under different conditions of visibility. In addition, the method has to be able to measure the river stage. This paper presents a camera-based measurement method for continuous measurement of river stage, flow velocity and flow rate. The system is currently running in more than 50 sites ranging from canals of 40 cm to rivers of more than 100 meters width. The developed technology can be implemented as an edge or cloud system. The cloud system only needs a camera with Internet connection to send videos to the cloud where they are processed, while the edge systems have a processing unit installed at the site where the processing is done.